Correlation Between Agility and Athletes Topspin of Table Tennis in Kendari City - Rahedin Suwo (JUARA : Jurnal Olahraga, 2020)
This research aims to determine the relationship between agility and the increase of athletes’ topspin ability of table tennis in Kendari City. This research used a quantitative approach and correlational technique. The population in this research were all athletes of Kendari City, amounting to 62 people from 2 clubs, namely PTM Maleo and PTM UHO, where PTM Maleo numbered 32 people consisting of 20 male athletes and 12 female athletes. While UHO PTM numbered 30 people consisting of 16 male and 14 female athletes. The sample in this research was taken using a purposive sampling technique that is with consideration of male, so the sample in this research amounted to 36 male athletes. To assess the results of the analysis using the correlation test. The results show that there is a strong correlation between agility in increasing table tennis topspin. That is, the more agile an athlete, the higher the ability of topspin. Therefore, the relationship between agility and increasing the ability of topspin athletes in Kendari City table tennis is very closely related.